1981
DOI: 10.4319/lo.1981.26.2.0382
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phytoplankton on iodine speciation in seawater

Abstract: In a study of the influence of cultured phytoplankton on iodine speciation in seawater, no appreciable interconversion of iodide and iodate was observed. The results suggest that phytoplankton, alone, are unlikely to influence iodine speciation in the ocean substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Unlike the results obtained in previous studies (Sugawara & Terada 1967, Truesdale 1978, Butler et al 1981, consistent depletion of iodate and concomitant appearance of iodide were found in this study in all the phytoplankton cultures at all concentrations of added iodate. This clearly indicates that all 6 phylogenetically diverse species of phytoplankton tested can induce the conversion of iodate and iodide.…”
Section: Conversion Of Iodate To Iodide By Phytoplanktonsupporting
confidence: 63%
See 2 more Smart Citations
“…Unlike the results obtained in previous studies (Sugawara & Terada 1967, Truesdale 1978, Butler et al 1981, consistent depletion of iodate and concomitant appearance of iodide were found in this study in all the phytoplankton cultures at all concentrations of added iodate. This clearly indicates that all 6 phylogenetically diverse species of phytoplankton tested can induce the conversion of iodate and iodide.…”
Section: Conversion Of Iodate To Iodide By Phytoplanktonsupporting
confidence: 63%
“…Fuse et al (1989) also suggested that iodide was preferentially taken up over iodate by several species of phytoplankton. Truesdale (1978) and Butler et al (1981), on the other hand, reported that no appreciable inter-conversion between iodate and iodide was observed in the cultures of several species of diatom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis grew out of the earlier finding by Egami & Sato (1947) that nitrate reductase is capable of reducing iodate under physiological conditions. Contrastingly, a number of studies found no relationship between iodine and biological activity or only observed iodide increases in phytoplankton cultures at iodate concentrations 10-fold greater than those naturally found (Truesdale 1978b, Butler et al 1981. A detailed study into the nitrate reductase hypothesis in which cells were grown on ammonia and the enzyme was deactivated by replacing molybdenum with tungsten in the growth media showed that iodate reduction was relatively insensitive to the function of nitrate reductase.…”
Section: Introductionmentioning
confidence: 94%
“…However, the evidence is inconsistent, with some reporting that algal cultures readily reduce iodate to iodide (Sugawara & Terada, 1967;Moisan et al, 1994;Wong et al, 2002;Chance et al, 2007) and others reporting minimal or no such reduction (Truesdale, 1978;Butler et al, 1981). A similar situation has developed in respect of field investigation.…”
Section: Introductionmentioning
confidence: 84%